Aspartate transaminase–platelet ratio and Fibrosis‐4 indices as effective markers for monitoring esophageal varices in HIV/hepatitis C virus co‐infected patients due to contaminated blood products for hemophilia. Issue 12 (19th February 2017) - Natsuda, Koji; Takatsuki, Mitsuhisa; Tanaka, Takayuki; Soyama, Akihiko; Adachi, Tomohiko; Ono, Shinichiro; Hara, Takanobu; Baimakhanov, Zhassulan; Imamura, Hajime; Okada, Satomi; Hidaka, Masaaki; Eguchi, Susumu
Abstract : Aim: We examined the feasibility of the aspartate transaminase (AST)–platelet ratio index (APRI) and Fibrosis‐4 (FIB4) score, which are well‐established markers for liver fibrosis, as indicators for monitoring esophageal varices in patients who were co‐infected with HIV and hepatitis C virus (HCV) due to contaminated blood products for hemophilia in Japan. Methods: Forty‐three HIV/HCV co‐infected patients were enrolled. All were hemophilic men (median age 41 years; range, 29–66 years). We analyzed the correlations between fibrosis indices (APRI, FIB4) and various liver function tests, fibrosis markers, liver stiffness measured by acoustic radiation force impulse elastography, and the findings of gastrointestinal endoscopy. Results: Both APRI and FIB4 were well correlated with several of the factors related to liver fibrosis and the existence of esophageal varices in the patients. The cut‐off values for detecting esophageal varices estimated as the area under the receiver operating characteristic curve were 0.85 for APRI and 1.85 for FIB4. Conclusion: In patients co‐infected with HIV/HCV due to contaminated blood products for hemophilia, APRI and FIB4 are effective for monitoring esophageal varices, even among patients who are apparently doing well with good liver function as Child–Pugh grade A.